A comparison of static and dynamic cerebral autoregulation during mild whole-body cold stress in individuals with and without cervical spinal cord injury: a pilot study. Issue 5 (May 2018) - Scheer, Jan; Kamijo, Yoshi-Ichiro; Leicht, Christof; Millar, Philip; Shibasaki, Manabu; Goosey-Tolfrey, Victoria; Tajima, Fumihiro
Abstract Study design Experimental study. Objectives To characterize static and dynamic cerebral autoregulation (CA) of individuals with cervical spinal cord injury (SCI) compared to able-bodied controls in response to moderate increases in mean arterial pressure (MAP) caused by mild whole-body cold stress. Setting Japan Methods Five men with complete autonomic cervical SCI (sustained > 5 y) and six age-matched able-bodied men participated in hemodynamic, temperature, catecholamine and respiratory measurements for 60 min during three consecutive stages: baseline (10 min; 33 °C water through a thin-tubed whole-body suit), mild cold stress (20 min; 25 °C water), and post-cold recovery (30 min; 33 °C water). Static CA was determined as the ratio between mean changes in middle cerebral artery blood velocity and MAP, dynamic CA as transfer function coherence, gain, and phase between spontaneous changes in MAP to middle cerebral artery blood velocity. Results MAP increased in both groups during cold and post-cold recovery (mean differences: 5–10 mm Hg; main effect of time:p  = 0.001). Static CA was not different between the able-bodied vs. the cervical SCI group (mean (95% confidence interval (CI)) of between-group difference: −4 (−11 to 3) and −2 (−5 to 1) cm/s/mm Hg for cold (p  = 0.22) and post-cold (p  = 0.24), respectively). At baseline, transfer function phase was shorter in the cervical SCI group (mean (95% CI) of between-group difference: 0.6 (0.2 to 1.0) rad;p  = 0.006), while between-group differences in changes in phase were not different in response to the cold stress (interaction term:p  = 0.06). Conclusions This pilot study suggests that static CA is similar between individuals with cervical SCI and able-bodied controls in response to moderate increases in MAP, while dynamic CA may be impaired in cervical SCI because of disturbed sympathetic control.